(untitled) (Bangladesh Medical Journal, 2014)
Osteogenesis Imperfecta is a inherited disease of connective tissue. Its hallmark feature is bone fragility with a tendency to fracture from minimal trauma or from the work of bearing weight against gravity. The disorder may occur in one out of 20,000 to one out of 60,000 live births, affecting both male and female of all races. We present a 38 year lady who gave birth to baby with osteogenesis imperfecta in Sir Salimullah Medical College & Mitford Hospital, Dhaka. Both lower limbs appeared shortened with thick musculo-cutaneous folds. Both the femoral shafts were shortened, deformed and fragmented. Both the humeral and fibular shafts were deformed and the presentation was breech. Her sclerae was blue. X-ray showed multiple fractures in humerus, femur and ribs and also right sided pulmonary hypoplasia. DOI: http://dx.doi.org/10.3329/bmj.v43i1.21376 Bangladesh Med J. 2014 January; 43 (1): 30-32